Curriculum Renewal for Evidence-based Practice in Australasian Optometry (Evidence-based Optometry Project) : Final Report. - Jalbert, Isabelle; Suttle, Catherine; Challinor, Kirsten; Junghans, Barbara; Pianta, Michael; Murray, Elizabeth; Thompson, Rachel; Jacobs, Rob; Togher, Leanne (Office for Learning and Teaching, 2014)
In the profession of optometry, responsibilities for eye and general health care make evidence-based practice (EBP) essential. Current optometry curricula include isolated teaching and learning strategies that aim to develop the knowledge and skills required for EBP, but recent pilot work suggests that optometry graduates have not uniformly adopted EBP. This project: Examines current optometry curricula and develop strategies for EBP learning and teaching in optometry; Develops an optometry- specific test of EBP knowledge and skills; Designs and implements an optometry-specific online resource to support EBP learning and teaching, accessible to all Australasian optometry schools; Using the resource, embeds strategies into the curricula as appropriate; and Measures competency in EBP pre- and post-curriculum renewal in optometry students. These processes are informed by discussions with stakeholders and by academics from other health disciplines with proven expertise in curriculum design for the learning and teaching of EBP. This is the final report from the project.